Research on the possibilities of a therapeutic approach through physical interventions with Laser MLS (Multiwave Locked Sys-tem) in post-combustion pathology (burns and severe burns) (Balneo and PRM Research Journal, 2022)
Abstract:Introduction. Depending on their severity, most of the burns are "particularly disabling injuries", which is why a constant improvement of current therapeutic interventions is necessary [1]. The patient describes the severe burn as the "ultimate agony" placing an important responsibility on the medical staff to achieve a satisfactory level of recovery and reintegration into society [2]. "Burns negatively influence the main aspects of life", but also the quality of life [3]. Laser therapy has stood out in recent years in stimulating the healing process of burn patients [4]. The role of this study is to highlight the therapeutic effects of the MLS LASER in the case of burns and severe burns.Methods. We previously carried out a systematic review of the related literature through the method of filtering and selecting profile documentary material, widely used and accepted at the international level: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Thus, we searched, using contextually, combinations/syntaxes of search keywords in the following international databases: Elsevier, PubMed, PMC, PEDro, articles published in English in ISI indexed journals Web of Knowledge/Science, during 01.01.2021-31.12.2021.Results and discussion. Seven of the selected articles have been included in our systematic literature review. The evolution of burn injuries materialized through improvements, will hopefully be achievable, both through direct observation and through the favorable dynamic progress of the scores of the quantification scales used: (VSS – Vancouver Scar Scale, VAS – Visual Analogue Scale, 5-D ITCH Scale, according to the model of the American Spinal Injury Association Impairment Scale – AIS - for sensitivity disorders, 3-step scale, ROM – Range of motion, MMT – Manual Muscle Test Scale, The Barthel Index, FIM – Functional Independence Measure scale, ADL, Timed up and go test, Walk Speed, Berg Balance Scale, Six-Minutes Walk Test). If it will be possible, sufficiently sustained medium/long-term follow-up of the cases included in our doctoral research will also be measured by the frequency of readmissions.Conclusions. Through this research, which is part of the doctoral study, we hope to be able to deepen aspects related to both the still existing limits and the identifiable possibilities for optimizing the conceptual and practical approach to patients with such pathologies.Keywords: Burns, MLS LASER, Burn wound, Burn Rehabilitation, Multiwave Locked System.